Efeitos do diferencial de juros, da depreciação cambial e do produto sobre a posição de investimentos e o nível de reservas no caso do Brasil - Souza, Francis Robert de (2019)
The dissertation takes as reference a paper by Olivier Jeanne on the macroprudential role of international reserves (American Economic Review: Papers & Proceedings 2016, 106 (5): 570 – 573), in which the Brazilian economy is identified as an example of the countercyclical use of capital control and the use of international reserves for the management of capital flows. The author seeks, in a model of intertemporal equilibrium, to identify the optimal conditions for maximizing the utility of a representative consumer in a emerging economy, in general. This work adopts the same methodology for the specific case of the Brazilian economy, adding to the model the variables GDP and exchange rate, to explain the variations in the differential between the foreign investment position and the international reserves level. It considers the period from the 4th quarter of 2001 to the 2nd quarter of 2018, on a multivariate time series econometric model, to assess the impact on the differential between the investment position and the foreign reserves level, caused by variations in exchange rate, GDP, and the EMBI+Br index levels.